The Role of Large Players in a Dynamic Currency Attack Game - Mei Li; Frank Milne (Queen's University, Department of Economics, 2007)
We establish a dynamic currency attack model in the presence of a large player (LP) based on Abreu and Brunnermeier (2003), which differs from most existing one-period static currency attack models. In an attack on a fixed exchange rate regime with a gradually overvaluing currency, both the inability of speculators to synchronize their attack and their incentive to time the collapse of the regime lead to the persistent overvaluation of the currency. We find that the presence of an LP, who is defined as a speculator with more wealth and superior information, can accelerate or delay the collapse of the regime, depending on his incentives to preempt other speculators or to "ride the overvaluation". When an LP's incentive to preempt other speculators is dominant, the presence of an LP will accelerate the collapse of the regime. However, when an LP's incentive to "ride the overvaluation" is dominant, the presence of an LP will delay the collapse of the regime. The latter case provides valuable insights into the role that LP's play in currency attacks: It differs from the usual perception that the presence of LPs will facilitate arbitrage in an asset market and alleviate asset mispricing due to their capability and willingness to arbitrage.
Keywords: D80; F31; 330; Large Player; Currency Attack; Wechselkurssystem; Fester Wechselkurs; Spekulation; Wirtschaftliche Macht; Spieltheorie